Analisis laporan keuangan dalam menilai rasio dan kinerja keuangan pada pt bank artha graha internasional tbk periode 2019-2023 - Puspita, Ririnn Diyah (Maliki Interdisciplinary Journal, 2025)
Financial statement analysis is an important process in evaluating the company’s financial performances, especially in the banking sector which acts as a major pillar in economic stability. PT Bank Artha Graha Internasional Tbk is one of the national banks that continues to strive to maintain balanced performance through effective financial management. This study aims to analyze the bank’s liquidity, profitability, and solvency ratios during the 2019-2023 period using a descriptive quantitative approach. The data used comes from the company’s annual financial statements accessed from official sources. The results showed that the Loan to Deposit Ratio (LDR) was at a stable level, reflecting a maintained liquidity capability. However, Return on Assets (ROA) and Return on Equity (ROE) showed significant fluctuations, especially at the beginning of the study period, before improving in subsequent years. The Capital Adequacy Ratio (CAR) was consistently above the regulatory minimum, indicating adequate capital strength as well as operational efficiency (Operating Expenses to Operating Income/BOPO). This research provides strategic recommendations to improving bank’s profitability and operational efficiency.